The Experience of Painting Art as an Effort to Foster Children's Creativity - Fajrie, Nur; Nashan, Syafiq; Wijayanto, Wasis (Kepompong Children Centre Journal, 2024)
The experience of art in panting plays a significant role in fostering children’s creativity, as it involves deep exploration, imagination, and self-expression. The panting process allows children to express their ideas and emotions visually, thereby aiding the development of creative thinking skills. This study aims to illustrate how the experience of panting can serve as an effective means to stimulate children's creativity from an early age. Using a descriptive qualitative approach, data were collected through observations and interviews with children engaged in panting activities, as well as through examining their artwork. The results indicate that the experience of panting provides children with space to try new techniques, create color combinations, and produce unique forms according to their imagination. Additionally, this activity helps children enhance their problem-solving skills, as they often encounter challenges such as panting objects they have never seen or creating stories based on their artwork. In the panting process, the role of companions, such as parents or teachers, is highly significant in encouraging children to keep exploring and feel confident in their creations. Panting activities also prove to improve focus, patience, and pride in the finished work, all of which contribute to children’s overall personality development. In conclusion, the experience of panting is not merely a recreational activity but also a vital medium for nurturing children’s creativity. By providing a supportive environment that encourages exploration, children can develop their creative potential to the fullest, which will be beneficial in their future lives.